Effect of heating on bonding characteristics for copper wire bond technology / Gurbinder Singh - Gurbinder , Singh (2021)
In recent years, copper has increasingly been used to replace gold to create wire interconnections in microelectronics. While the industry is continuously working on this transition from gold to copper wire to reduce costs, the challenge remain in producing robust and reliable joints for semiconductor devices. The use of copper wire is known to pose threats to devices with thin structures. The impact of hard copper free air ball onto bonding surfaces is undesirable as it can damage the bond pad and the die structure. Since copper requires higher bonding force and excessive ultrasonic energy to create a bond, this research investigates the effect of pedestal and free air ball heating on copper wire bonds. Wire bonding was performed on bond pads consisting of NiPdAu metallization under sixteen different pedestal temperatures. This research also investigates the effects free air ball laser heating on bonding strength and microstructural quality. Results have shown, ball shear strength for copper wire varies linearly with the increase of pedestal temperature. The ball shear strength is the lowest at temperature 40°C and is gradually increased to an average of 25g at temperature 200°C. At pedestal temperature 340°C, average ball shear strengths of 35g was achieved. EBSD analysis indicated the cell-structured zone in the laser-assisted sample is wider near the bonding, whereas, in the laser free FAB sample, two intense deformation zones formed. The results of this research will be of advantage to semiconductor plastic packaging. Copper wire bonding quality can be further improved without the need to use excessive bonding temperature, higher bonding force and excessive ultrasonic energy.